2014
DOI: 10.3324/haematol.2013.096362
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of LAIR1 (CD305) as assessed by flow cytometry in a prospective series of patients with chronic lymphocytic leukemia

Abstract: ABSTRACTexpressed in early stages of CLL than in advanced CLL 17 and that its expression is lower in patients with high-risk CLL. 16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
(39 reference statements)
4
24
0
Order By: Relevance
“…Unfavorable prognostic factors include male gender, an initial white blood cell count above 35 × 10 9 /L, lymphocyte doubling time (LDT) of less than six months, a diffuse histological pattern in bone marrow infiltration 35 and elevated levels of beta-2 microglobulin, LDH, serum thymidine, and serum CD23 at diagnosis 36 . As previously discussed, high expressions of CD38, 29 CD49d, 37 CD305, 38 and ZAP-70 protein detected by flow cytometry are also prognostic markers 31 . However, these markers are no more sensitive than clinical staging for determining tumor burden and predicting disease progression.…”
Section: Prognosismentioning
confidence: 99%
“…Unfavorable prognostic factors include male gender, an initial white blood cell count above 35 × 10 9 /L, lymphocyte doubling time (LDT) of less than six months, a diffuse histological pattern in bone marrow infiltration 35 and elevated levels of beta-2 microglobulin, LDH, serum thymidine, and serum CD23 at diagnosis 36 . As previously discussed, high expressions of CD38, 29 CD49d, 37 CD305, 38 and ZAP-70 protein detected by flow cytometry are also prognostic markers 31 . However, these markers are no more sensitive than clinical staging for determining tumor burden and predicting disease progression.…”
Section: Prognosismentioning
confidence: 99%
“…Clinical significance of the expression of leukocyte‐associated immunoglobulin‐like receptor‐1 (LAIR1, CD305), an inhibitor of B‐cell receptor‐mediated signaling, has been reported in chronic lymphocytic leukemia. Downregulation of LAIR1 was observed in high‐risk CLL, respectively . According to gene expression‐activated B cells, CD22 low CD25 + seems to be genetically closer to WM‐BC, as GEP analysis showed only 51 downregulated genes in WM‐BC …”
Section: Wm B‐cell Clone Molecular Biology: Similarity To Normal B Cellsmentioning
confidence: 98%
“…However, based on clinical (e.g., stage and doubling time), phenotypic, and genetic features, it can be completely indolent or quite aggressive. Specifically, the overall expression of CD38, ZAP70, LAIR1, and CD49d biomarkers, though not univocally, indicates an activation of the leukemic B cell and it is related to a worse outcome . In addition, immunohistological analyses have demonstrated that the identification of abundant proliferating centers is associated to a worse behavior .…”
mentioning
confidence: 99%